Settler-Colonialism, Memoricide and Indigenous Toponymic Memory: The Appropriation of Palestinian Place Names by the Israeli State - Masalha, Nur (Journal of Holy Land and Palestine Studies, 2015)
Cartography, place-naming and state-sponsored explorations were central to the modern European conquest of the earth, empire building and settler-colonisation projects. Scholars often assume that place names provide clues to the historical and cultural heritage of places and regions. This article uses social memory theory to analyse the cultural politics of place-naming in Israel. Drawing on Maurice Halbwachs' study of the construction of social memory by the Latin Crusaders and Christian medieval pilgrims, the article shows Zionists' toponymic strategies in Palestine, their superimposition of Biblical and Talmudic toponyms was designed to erase the indigenous Palestinian and Arabo-Islamic heritage of the land. In the pre-Nakba period Zionist toponymic schemes utilised nineteenth century Western explorations of Biblical names' and places' and appropriated Palestinian toponyms. Following the ethnic cleansing of Palestine in 1948, the Israeli state, now in control of 78 percent of the land, accelerated its toponymic project and pursued methods whose main features were memoricide and erasure. Continuing into the post-1967 occupation, these colonial methods threaten the destruction of the diverse historical cultural heritage of the land.